Tranexamic acid in major trauma: implementation and evaluation across South West England. (February 2017) - Paudyal, Priyamvada; Smith, Jason; Robinson, Maria; South, Adrian; Higginson, Ian; Reuben, Adam; Shaffee, Julian; Black, Sarah; Logan, Stuart
Abstract : Objective: To carry out a prospective evaluation of tranexamic acid (TXA) use in trauma patients. Patients and methods: TXA was introduced to all emergency ambulances and emergency departments in the South West, UK, on 1 December 2011. We carried out a prospective evaluation of TXA use in trauma patients in the South West Peninsula between December 2011 and December 2012. We collected prehospital and hospital data on TXA administration using the Trauma Audit Research Network database. Data on prehospital administration of TXA were cross-checked with the South Western Ambulance Service Trust. Data were analysed using SPSS (version 20). Results: Altogether, 82 patients were administered TXA during the study period. The median age of the patients was 49 years (IQR 30, 66), and 72% were men. One-third of the patients arrived at hospital by air ambulance. During the first 3 months, administration of TXA was limited to one patient each month receiving the drug. However, an upward trend was observed after June until October 2012, with the increment being more than 10 fold in July, September and October 2012. Conclusion: This is the first study to evaluate the use of TXA in civilian practice in the UK. Our study shows that ambulance service personnel and emergency departments can effectively administer TXA.